Social Media Influence on Senior High Students' Spending Behavior for a Financial Management Plan - Joel Mark Rodriguez; Christine Velez; Lourdes Palallos (International School for Social and Business Studies, 2024)
Purpose: This paper focuses on the rising influence of social media on senior high school students' financial behaviour and uses the case study of a Manila student subjected to social expectations, attitude in spending, and perceived control. Social media is viewed as a new learning opportunity about finance, yet it tends to nurture consumerist tendencies associated with impulsive buying. Therefore, the research gap in the existing studies aims at detailing mechanisms by which social media impacts students' spending. Study design/methodology/approach: A descriptive-correlational design was used, with responses obtained from 308 senior high school students through structured questionnaires. This allowed for assessing the correlations between social media influence, students' financial attitudes, subjective norms, perceived control, and spending behaviour patterns. Findings: Key findings depict a good correlation between students' exposure to social media and their spending behaviour, which would articulate how digital platforms influence financial attitudes and decision-making. Integrating educational finance management into school curricula would support students in learning to think critically and responsibly about their finances. However, this cross-sectional study limits generalisation and calls for the agenda of longitudinal research in this area. Originality/value: This paper contributes to the existing literature based on particular mechanisms about the impact of social media on student spending behaviour, especially within the context of Manila. It indicates the practical value of infusing financial education into school programs, promoting media literacy and financial responsibility in students to foster independence and long-term fiscal awareness.